THE INTERNATIONAL LAW PERSPECTIVE ON THE ESPIONAGE OF AUSTRALIA TO INDONESIA - Yudha Setya Negara (FH 15 UMY 140, 2015)
*140 Espionage among nations is an exceptionally old and extensive human endeavor which is done in various fields. Espionage is current not only between countercurrent in terms of political opponents, but also between countries that are friendly and cooperative in global arena. International law has long addressed the issue of espionage during times of war while peacetime espionage has remained unaddressed. Australian intelligence tried to listen into Indonesian president Susilo Bambang Yudhoyono's mobile phone Australia's spy agencies have attempted to listen in on the personal phone calls of the Indonesian president and have targeted the mobile phones of his wife, senior ministers and confidants, a top-secret document from whistle-blower Edward Snowden. The surveilling government have violated basic expectations of privacy, and another problem is that one obvious source of regulations that is International law has little to say about foreign surveillance